Pelatihan Pemanfaatan Google site Sebagai Media Pembelajaran Pemasaran Produk untuk Peserta Magang di EG Komputer - Darso Darso; Iqbal Tri Zulian; Ajiono Ajiono; Ujiani Ujiani (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Information technology is currently developing very rapidly. This makes an impact on various aspects. One that is affected is the marketing aspect. This service activity aims to utilize online media, namely the google site for marketing media for MSME products. The materials presented in this training include the use of google site for online marketing and tutorials on how to create a website with the google site. The number of participants in this training on the use of the google site is 20 people, as for the implementation time, which is on July 2-3, 2022. The method used is identification, providing solutions to problems, filling out materials, then continuing with direct practice and discussions. The result of this training is that interns are expected to be able to create a website to support product marketing and increase product sales and can be widely known through online media by utilizing the google site.